Perancangan dan Pembuatan Mesin Roll Press Cutting Otomatis Penggiling Adonan Mie - Rosita Dewi Pratiwi; Tri Tiyasmihadi; Pranowo Sidi (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
One of the supporting factors in making noodles is the milling machine. The most modern grinding machine is a motorized noodle grinding machine. But the working process is not optimal because the process of piping and cutting the dough goes apart. Therefore, the automatic noodle grinder dough grinding press press machine (MRPCOPAM) was made. MRPCOPAM has an automatic work process, where the flattened mixture will run directly into the cutting roll. The motor used is a single phase AC motor with a rotating speed of 2800 rpm, which is then reduced to 35 rpm with the help of a 1:80 gear box. The piping roll used is Ã˜25 mm and the cutting roll is Ã˜17 mm. The main gear pitch pitch is 18.75. Rear gears for the piping roll have a pitch of 27mm. Rear gears for cutting roll pitch 15mm in diameter.